"They Never Really Leave Us": Transcendent Narratives About Loss Resonate With the Experience of Severe Grief. (11th February 2022) - Das, Enny; Peters, Judith
Abstract: Self-transcendent media experiences can instill a sense of connectedness, the sense of being part of a bigger whole. Proposing that this experience is relevant for people who have lost a loved one, the present research examined processing and effects of transcendent narratives of loss among the bereaved. Study 1 (N = 1, 012) examined if personal experience with loss (grief severity, loss acceptance) increased mixed affect, transportation, identification, and appreciation of narratives of loss with, and without a reference to transcendence; Study 2 (N = 240) examined effects on elevation and connectedness. Findings showed that transcendent narratives of loss increased transportation, identification, and story appreciation especially for individuals with severe grief. Conversely, transcendent narratives of loss increased elevation, and connectedness especially for individuals with low grief. Findings suggest that transcendent narratives of loss resonate with severe personal grief. We found no evidence that a transcendent perspective on death reflects difficulty in accepting one's personal loss.